Analysis of the stock status of red snapper (Lutjanus malabaricus) in Saleh Bay, West Nusa Tenggara Province, Indonesia - LORA SANTIKA; SITTI HILYANA; SORAYA GIGENTIKA; SYAEFUL BACHRI; MISBAHUL UMAM (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Santika L, Hilyana S, Gigentika S, Bachri S, Umam M. 2026. Analysis of the stock status of red snapper (Lutjanus malabaricus) in Saleh Bay, West Nusa Tenggara Province, Indonesia. Biodiversitas 27 (4): d270417. https://doi.org/10.13057/biodiv/d270417. The red snapper (Lutjanus malabaricus) is a demersal fish species of high economic value in Indonesia, including in Saleh Bay, Sumbawa, West Nusa Tenggara. Increasing fishing pressure has raised concerns regarding its stock status and sustainability. This study aims to assess the stock condition of L. malabaricus in Saleh Bay as a basis for sustainable fisheries management. The analysis was conducted using the Length-Based Spawning Potential Ratio (LBSPR) model applied to 11,945 individuals caught by small-scale fishers between 2017 and 2024. Data were obtained from the Marine and Fisheries Agency of West Nusa Tenggara Province and the Scientific Forum for Sustainable Fisheries Management (FIP2B), with access granted through a formal Data Sharing Agreement authorized by both institutions. The LBSPR model was run assuming a natural mortality to growth ratio (M/K) of 1.47 and logistic selectivity. Results showed an average fish length of 53.88 cm. Growth parameters were estimated with an asymptotic length (L∞) of 85.56 cm, a growth coefficient (K) of 0.22 year⁻¹, natural mortality (M) of 0.323 year⁻¹, and a theoretical age at zero length (t₀) of -0.5711 years. Length at first maturity (Lm) was 45.37 cm, while length at first capture was slightly higher at 47.26 cm. Spawning Potential Ratio (SPR) values fluctuated between 0.21 and 0.38 throughout the study period and declined steadily to 0.21 in 2024. In this study, stock status was interpreted using a precautionary reference point of SPR: 0.30. These results indicate that the red snapper stock in Saleh Bay has transitioned from lightly exploited to fully exploited conditions and is currently at risk of reduced reproductive potential. The findings highlight the need to strengthen management implementation, particularly through enforcement of minimum size regulations and improved control of fishing pressure, to support precautionary and adaptive management of red snapper fisheries in Saleh Bay.